Contribution of relative sea-level rise to bridge failure in the USA during Hurricane Ivan. Issue 4 (16th November 2020) - Webb, Bret M; Douglass, Scott; Cleary, John
Abstract : Highways in the coastal environment are subject to storm surge and wave hazards during extreme events. The magnitude of these hazards, and the subsequent vulnerability of transportation infrastructure, will change over time with relative sea-level rise. These changes, which are often non-linear, lead to an amplification of storm-water levels and wave characteristics. These non-linear changes in storm surge and wave hazards, resulting from over three decades of relative sea-level rise between the time of bridge construction (1968) and the landfall of Hurricane Ivan (2004), contributed to span unseating and displacement along the Interstate 10 twin-span bridges over Escambia Bay, Florida, USA. A direct comparison of simulated hydrodynamics at failed bridge spans shows that 36 years of relative sea-level rise resulted in higher storm surge and larger wave heights and greater wave-induced loads. The increase (∼300 kN) in structural demand due to relative sea-level rise is nearly equal to the structural capacity provided by the minimal connections between the deck girders and bent beams. This finding underscores the importance of incorporating appropriate projections of relative sea-level rise into the design of major infrastructure, along with assessments of hazard risk over the expected service life of an asset.